1998
DOI: 10.1093/tropej/44.5.256
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of thyroxine-binding prealbumin, C-reactive protein and interleukin-6 in protein-energy undernourished children and normal controls without or with associated clinical infections

Abstract: We measured the levels of thyroxine-binding prealbumin (TBPA), C-reactive protein (CRP), and interleukin-6 (IL-6) in sera from protein-energy undernourished and control children either without or with associated clinical infections. Levels of TBPA were significantly lower in undernourished than in control children without clinical infections. Mean serum TBPA concentration was also significantly lower in both clinically infected undernourished and control children than in those of the same nutritional status bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0
12

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 0 publications
3
21
0
12
Order By: Relevance
“…increase due to stimulation of hepatic synthesis, depression of hepatic production of visceral transport proteins (negative acute phase proteins) like albumin, transferring, thyroxin binding prealbumin (TBPA) and retinol binding proteins (RBP) etc. occurs [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…increase due to stimulation of hepatic synthesis, depression of hepatic production of visceral transport proteins (negative acute phase proteins) like albumin, transferring, thyroxin binding prealbumin (TBPA) and retinol binding proteins (RBP) etc. occurs [8].…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of infection results in depression of their hepatic production as well as increased passage to the extra vascular space, consequently diminishing their serum levels making them markers for acute phase conditions [8].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that nutritional biochemical markers such as thyroxine binding pre albumin (TBPA) show a good relation to WAZ and HAZ scores (19), i.e. TBPA may be a useful marker to assess the effects of nutrition on thyroid size.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have suggested that malnutrition does not affect CRP production in response to infections. 33,34 In a study in Malawi, although children with kwashiorkor had reduced rates of protein breakdown and synthesis, their CRP levels were similar to those without kwashiorkor. 35 To our knowledge, only 1 study found that CRP levels in response to infection are lower in malnourished than in wellnourished children.…”
Section: Discussionmentioning
confidence: 99%